Update on the Host Range of Different Species of Fruit Flies in Indonesia - Suputa Suputa; Y. Andi Trisyono; Edhi Martono; Sri Suharni Siwi (Universitas Gadjah Mada, 2010)
Recent reviews on Dorsalis and Dacine fruit flies had implication on host-insect inventory, including in Indonesia. Update is needed because of these changes and due to the rising of fruit and vegetable trade within islands, as well as with neighboring countries. Fruits were collected over a 3-year period from 24 provinces of Indonesia, covering areas from Aceh to Papua. This work was done specifically to obtain detailed information regarding the host range of the important species of Bactrocera spp., Atherigona orientalis, and Dacus longicornis, as well as Adrama determinata. Male lure Steiner traps to attract fruit flies were used in this study as an additional method to support species variation.Atotal of 1125 fruit samples were collected from many locations. Thirty five plant species from 18 families were recorded as fruit fly hosts and 27 plant species were new report as specific host for certain species of fruit fly. A larger array of host plants for fruit flies in Indonesia than reported before suggests the importance of effective quarantine measures to limit the spread of harmful fruit fly and to prevent the accidental introduction of invasive alien fruit fly species from other countries.